Some Remarks on the Semantic and Cultural Aspect of Emotive Phrasemes (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Emotional phrases are therefore essential to enrich language and effectively communicate our moods and our most intimate feelings. They help to strengthen emotional bonds between individuals by allowing more authentic and empathetic communication. In this article we analyzed the role of emotive phrasemes in human communication, the influence of culture on idiomatic expressions in French and Uzbek languages.